The Uprising in Kashmir - Ahmed, Abu Taher Salahuddin (KDI School, 1999)
This thesis is mainly about the Kashmiri Muslims’ uprising in India in 1989. The uprising is viewed as the internal conflict between the Indian state’s bad policies to repress the Muslim ethnic group in Kashmir and the Kashmiris’ challenge against such an authority of India. The puzzles that this thesis raises: Why did the uprising break out? As it broke out, why did it break out in 1989, and not before? The study identifies both underlying causes and triggering causes of the uprising. The central argument is that the current dimension of the Kashmiri uprising is the continuation of the past, and therefore, the endresult of the Indian government endemic “misrule” (underlying macro-political causal factor) in Kashmir. This, in turn, created sufficient grounds to assert their (Kashmiri Muslim) distinct separate Muslim identity (ethno-religious factor) making Kashmir a case of enthnonationalism. Enthnonationalism took roots because they sensed that they were relatively deprived from their rights and share. This sense of relative deprivation (economic and political factors) led to increasing ethnic/political mobilization (triggering micro-political causal factor) among Kashmiris, especially within the new-generation. Their awakening to the realization of relative deprivation and their efforts towards ethnic/political mobilization were made possible by high rate of literacy among the Kashmiris and their access to media: both audio and video and the “diffusion” effect from the similar incidents happening across the border. Although the current uprising is chiefly driven internally by the Indian elite’s bad policy (Brown’s leadership-centric approach), it is also reinforced by external factors. The external factors included the successful Iranian Revolution of 1979 (cultural/religious factor), the rise of the Palestinian Intifada movement and the eventual establishment of the Palestinian state (religio-cultural factor), the Soviet fiasco in Afghanistan (political factor), the ethnic-based uprising in the former Soviet Union and Yugoslavia (ethnonationalism factor), and more important, the Pakistani support (bad neighbor policy) for the Kashmiri rebels. These external factors were tangential to the uprising. The causal direction was bi-directional and not unidirectional. However, now that the genie, the uprising, has come out of the bottle, it will keep bedeviling the bilateral relations of India and Pakistan. The Kargil crisis of 1999 amply testified that. The 1989 uprising has transformed Kashmir into a new and ongoing area of conflict in which India, Pakistan, and the Kashmiri people all have a stake.
Thesis(Master) --KDI School:Master of International Relations and Political Economy,1999